1991
DOI: 10.1172/jci114984
|View full text |Cite
|
Sign up to set email alerts
|

Lack of HLA class I antigen expression by cultured melanoma cells FO-1 due to a defect in B2m gene expression.

Abstract: The melanoma cell line FO-1 does not express HLA class I antigens and does not acquire them on the cell surface after incubation with IFN--y. Immunochemical studies showed that FO-1 cells synthesize HLA class I heavy chain, but do not synthesize t#2-microglobulin (02-it). The latter abnormality is associated with lack of 82-mRNA which remains undetectable in FO-1 cells incubated with IFN-'y. The defect was identified as a genetic lesion in the B2m gene, since DNA hybridization analysis detected a deletion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
167
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(175 citation statements)
references
References 58 publications
8
167
0
Order By: Relevance
“…These heavy chains, 'free' of β 2 m, have been demonstrated to be either 'unfolded' (Allen et al, 1986;Smith et al, 1993), or at least partially folded (Machold et al, 1995), and to bear mature carbohydrates (Hansen et al, 1988;Machold et al, 1995). Biochemical and functional data in β 2 m knockout mice are consistent with the idea that both D b -and L d -free heavy chains may retain some ability to bind (Smith et al, 1993) and present (Lehmann-Grube et al, 1994;Cook et al, 1995) antigen even when synthesized in the absence of β 2 m. In contrast, there is no evidence that any of the more than 300 sequenced HLA-A and -B alleles might be constitutively expressed on the cell surface of most (Fellous et al, 1977;D'Urso et al, 1992;Gattoni-Celli et al, 1992;Wang et al, 1993;Bicknell et al, 1994;Porgador et al, 1997) β 2 m-defective cells of human origin.…”
supporting
confidence: 75%
See 3 more Smart Citations
“…These heavy chains, 'free' of β 2 m, have been demonstrated to be either 'unfolded' (Allen et al, 1986;Smith et al, 1993), or at least partially folded (Machold et al, 1995), and to bear mature carbohydrates (Hansen et al, 1988;Machold et al, 1995). Biochemical and functional data in β 2 m knockout mice are consistent with the idea that both D b -and L d -free heavy chains may retain some ability to bind (Smith et al, 1993) and present (Lehmann-Grube et al, 1994;Cook et al, 1995) antigen even when synthesized in the absence of β 2 m. In contrast, there is no evidence that any of the more than 300 sequenced HLA-A and -B alleles might be constitutively expressed on the cell surface of most (Fellous et al, 1977;D'Urso et al, 1992;Gattoni-Celli et al, 1992;Wang et al, 1993;Bicknell et al, 1994;Porgador et al, 1997) β 2 m-defective cells of human origin.…”
supporting
confidence: 75%
“…The previously defined HLA-A25 and -B8 specificities (D'Urso et al, 1992) were found to correspond to the HLA-A*2501 and -B*0801 alleles. HLA-C, for which no tissue typing is available, was genotyped as HLA-Cw*0701.…”
Section: Hla-a -B -C Genotyping Of Fo-1 Cellsmentioning
confidence: 70%
See 2 more Smart Citations
“…Our explanation for this finding could be that heavy chains recognized by HCA2 antibody (mainly of the HLA-A type) might be more stable at the cell surface in the absence of β2-m than the heavy chains recognized by HC10 (mainly of the HLA-B/C types). The underlying mechanism of β2-m weak expression could involve deletion or mutation in the β2-m gene, in analogy with other well studied tumours (Klein et al, 1967;Rosa et al, 1983;D'Urso et al, 1991;Bicknell et al, 1994). Alternatively, it could result from a post-translational mechanism such as sequestering of the β2-m protein by a viral or other protein, in analogy with the mechanism described for cytomegalovirus down-regulation of MHC class I molecules (Chapman and Bjorkman, 1998).…”
Section: Mhc Class I Expression In Osccsmentioning
confidence: 96%